Pola Tinggal, Perawatan Kebersihan Dan Kesehatan Lanjut Usia Dalam Rumah Tangga pada Komunitas Etnis Tionghoa di Pegunungan Saliung Singkawang Kalimantan Barat (Suatu Kajian Sosial Budaya) - ., Imran (Universitas Tanjungpura, 2012)
Background: The increasing number of elderly becomes the main problem related with physical, economy and social conditions. Elderly who lives in isolated area will aggravate their living process. Community of Tionghoa ethnic who live in the Saliung mountain is a group of community who have ever been eliminated socially or politically. Objective: This research was aimed to find out problems that related with way of living, hygiene and health codition of elderly in the household of Tionghoa ethnics community. Method: This was a qualitative research that used social culture approach and intrinsic case study (participatory) design. This research was implemented in Saliung mountain range in the village of Sedau, sub district of South Singkawang, West Kalimantan. The sought variable was way of living, knowledge, attitude and personal hygiene and health behavior. Information was obtained from elderly, community, health officer, village officials, tradition and culture institution that oriented on triangulation. Data was presented in the form of diagram, documentation, direct reference and description. Result: This research was succeed in exploring knowledge, attitude and behavior of elderly in the household and various aspects that were related with the living of elderly and community of Tionghoa ethnic generally, including personal hygiene as the effect of high work productivity so that time and opportunity is very limited for for personal care. Conclusion: Problems of way of living, personal hygiene and health condition of Tionghoa ethnic community in Saliung mountain were related with perspectives in order health intervention to succeed.